2010
DOI: 10.1523/jneurosci.1754-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Terminals in the Nucleus Accumbens But Not the Dorsal Striatum Corelease Glutamate

Abstract: Coincident signaling by dopamine and glutamate is thought to be crucial for a variety of motivated behaviors. Previous work has suggested that some midbrain dopamine neurons are themselves capable of glutamate corelease, but this phenomenon remains poorly understood. Here, we expressed the light-activated cation channel Channelrhodopsin-2 (ChR2) in genetically defined midbrain dopamine neurons to stimulate exocytosis specifically from dopaminergic terminals in both the nucleus accumbens (NAc) shell and dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
485
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(537 citation statements)
references
References 25 publications
39
485
2
Order By: Relevance
“…A subset of DA neurons in the VTA co-releases DA and glutamate in the NAc shell (21)(22)(23). We recently showed that the release properties and the modulation by G i -coupled D 2 receptors are remarkably similar for DA and glutamate release from these terminals (20).…”
Section: B6mentioning
confidence: 99%
“…A subset of DA neurons in the VTA co-releases DA and glutamate in the NAc shell (21)(22)(23). We recently showed that the release properties and the modulation by G i -coupled D 2 receptors are remarkably similar for DA and glutamate release from these terminals (20).…”
Section: B6mentioning
confidence: 99%
“…It is also possible that KOR modulates other glutamatergic projections to the mPFC we did not explore here, such as the thalamus. A proportion of dopamine (DA) neurons co-express the glutamate transporter (Yamaguchi et al, 2011) and have been shown to co-release glutamate in the ventral striatum (Stuber et al, 2010;Tecuapetla et al, 2010). Electrical and chemical activation of the VTA produces fast glutamatergic synaptic responses in the mPFC (Lavin et al, 2005), suggesting that mesocortical DA neurons may also co-release glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing evidence, primarily from cultured DA neurons, had indicated that glutamate could be synthesized and released by DA neurons [147,148]. Using optogenetic methods with selective expression of channelrhodopsin (ChR2) in DA neurons, several groups have now shown that glutamate released from DA axons produces glutamate receptor-dependent excitatory postsynaptic currents in striatal neurons in ex vivo slices [149][150][151][152][153][154] and mediates behavioural consequences in vivo [155]. Similar methods have shown that co-release of GABA from DA axons produces GABA A receptor-dependent IPSCs in striatal neurons, although DA neurons do not synthesize GABA but rather obtain it via plasma membrane uptake [152,156].…”
Section: Modulation Of Somatodendritic Dopamine Release By Synaptic Imentioning
confidence: 99%